PENERAPAN PIDANA OLEH HAKIM TERHADAP TERDAKWA TINDAK PIDANA PERTAMBANGAN TANPA IZIN DALAM KAWASAN HUTAN - Madjid, Neni Vesna; Putra, Mekky (Universitas Ekasakti, 2023)
The judge's considerations in applying the crime to the defendant for the criminal act of mining without a permit in a forest area in Decision No.42/Pid.Sus/2020/Pn.Kbr legally fulfill the element of carrying out production to obtain gold which is a metal mineral group mining commodity without a permit, which regulated in Article 158 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining in conjunction with Article 55 paragraph (1) 1st of the Criminal Code. Non-juridically, it is an aggravating situation where the actions of the Defendants can result in environmental damage. In Decision number 167/Pid.Sus/2021/Pn.Kbr legally the Judge's consideration is fulfilling the element of participating in committing a crime, namely acting as a helper whose job is to refuel and clean 1 unit of excavator. Criminal Application by Judges Against Perpetrators of Criminal Acts of Mining Without Permits in Forest Areas in Decision No.42/Pid.Sus/2020/Pn.Kbr namely Convicting criminals with imprisonment for 6 (six) months each and a fine of each Rp. 5,000,000.00 (five million rupiah) with the provision that if it is not paid, it will be replaced with confinement for 5 (five) days. Verdict No. 167/Pid.Sus/2021/Pn. Kbr. decided to participate in mining without a permit.